2021
DOI: 10.7759/cureus.13631
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic External Pelvimetry Test in Third Trimester Pregnant Women: Shifting Positions Affect Pelvic Biomechanics and Create More Room in Obstetric Diameters

Abstract: Dystocia in labor is still a clinical challenge. The "contracted pelvis" is the absence of pelvic mobility, which leads to fetal-pelvic disproportion, obstructed labor, and operative delivery. Maternal pelvis biomechanics studies by high technological techniques have shown that maternal shifting positions during pregnancy and labor can create more room in the pelvis for safe delivery. The external and internal pelvic diameters are related. The present study aims to evaluate the external obstetric pelvic diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 24 publications
5
17
0
Order By: Relevance
“…The difference in amplitude between maternal positions of the bi-cristal diameter was statistically different between the two groups studied. Specifically, when we compared the measurements taken in the standing p1 position to those obtained in the "hands-and-knees" p2 position, the diameter decreased in the obstructed labor group, while it increased in the control group, in agreement with our previous results (Table 5) [15]. However, in the squat position, the bi-cristal diameter decreased more in the control group than in the obstructed labor group.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The difference in amplitude between maternal positions of the bi-cristal diameter was statistically different between the two groups studied. Specifically, when we compared the measurements taken in the standing p1 position to those obtained in the "hands-and-knees" p2 position, the diameter decreased in the obstructed labor group, while it increased in the control group, in agreement with our previous results (Table 5) [15]. However, in the squat position, the bi-cristal diameter decreased more in the control group than in the obstructed labor group.…”
Section: Discussionsupporting
confidence: 89%
“…Our previous studies showed the ability of external obstetric pelvimetry to measure the maternal diameters in different positions. We found that as the woman changed her posture, the diameters varied, affirming the findings of studies that used high-tech methods to obtain these measurements [ 15 , 16 ].…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations